Uromodulin: a new biomarker of fetal renal function? - Thais Emanuelle Faria Botelho; Alamanda Kfoury Pereira; Patrícia Gonçalves Teixeira; Eura Martins Lage; Gabriel Costa Osanan; Ana Cristina Simões e Silva (Brazilian Journal of Nephrology)
Abstract Introduction: Obstructive uropathies are main diseases affecting the fetus. Early diagnosis allows to establish the appropriate therapy to minimize the risk of damage to kidney function at birth. Biochemical markers have been used to predict the prognosis of renal function in fetuses. Uromodulin, also known by Tamm-Horsfall protein (THP) is exclusively produced in the kidneys and in normal conditions is the protein excreted in larger amounts in human urine. It plays important roles in kidneys and urinary tract. Also it participates in ion transport processes, interact with various components of the immune system and has a role in defense against urinary tract infections. Moreover, this protein was proved to be a good marker of renal function in adult patients with several renal diseases. Objective: To evaluate if uromodulin is produced and eliminated by the kidneys during fetal life by analyzing fetal urine and amniotic fluid and to establish correlation with biochemical parameter of renal function already used in Fetal Medicine Center at the Clinic Hospital of UFMG (CEMEFE/HC). Methods: Between 2013 and 2015, were selected 29 fetuses with indication of invasive tests for fetal diagnosis in monitoring at the CEMEFE/HC. Results: The determination of uromodulin was possible and measurable in all samples and showed statistically significant correlation with the osmolarity. Conclusion: There was a tendency of lower levels of Uromodulin values in fetuses with severe renal impairment prenatally. Thus, high levels of this protein in fetal amniotic fluid or fetal urine dosages possibly mean kidney function preserved.